An alternative approach to addressing learning losses in mathematics using differentiated instruction strategy - Mutlu, Yilmaz; Kalayci, Ozlem; Otken, Sule; Polat, Kubra; Durmaz, Burcu (Routledge Journals, Taylor & Francis Ltd, 2026)
This mixed-method study, based on an embedded design, aims to examine the effectiveness of differentiated teaching strategies used to address learning losses in mathematics, which play a vital role in middle school students' future educational lives. The study applied quantitative data for 145 students selected from 5th to 8th grade age 10-14 years, and qualitative data for 10 middle school mathematics teachers. The quantitative data obtained from the experimental process were analyzed using Wilcoxon signed-Rank test, and the qualitative data analyzed through content analysis. The findings indicated a significant improvement in students' learning losses in mathematics across all grades, except for sixth grade. The results revealed that, despite initial difficulties, tasks grounded in differentiated teaching strategies addressed the instructional needs of students by adapting to their readiness levels, areas of interest, and diverse learning tendencies in mathematics. However, teachers emphasized that limited instructional time, a dense curriculum, and large class sizes constrained the effective implementation of differentiated instruction strategies. In conclusion, differentiated instruction can be considered a promising approach for addressing learning losses in mathematics among middle school students in mixed-ability classrooms. The study suggested professional development opportunities and access to resources are needed by teachers for effective implementation of differentiated teaching strategy.
Keywords: Differentiated Instruction Strategy; Learning Loss; Mathematics Teaching; Tiered Instruction Technique